Providing palliative care closer to home: a retrospective analysis from a remote Australian hospital. Issue 1 (14th January 2020) - Watson, Benjamin J.; Budd, Richard; Waran, Eswaran; Scott, Ian; Quilty, Simon
Abstract: Background: Rural and remote patients have reduced access to palliative care, often resulting in inter‐hospital transfers and death a long way from home and family. Katherine Hospital (KH), a 50‐bed hospital services a population with high Aboriginality who experience this issue. Aims: To characterise trends in mortality and transfers at a remote hospital in reference to increasing capacity to provide palliative care. Methods: Retrospective analysis of deaths in patients over 18 years of age, admitted between 2008 and 2018 at KH, Northern Territory. Outcome measures include number of deaths, aeromedical transfers to tertiary facility, palliative care episodes, demographics including Aboriginality, admission data and comorbidity. Statistical analysis included unpaired t ‐test, chi‐square test and regression analysis. Results: The number of deaths in KH increased from 23 (0.88% of inpatient admissions) in 2011 to 52 in 2018 (1.7%). During the same period, the proportion of all deaths classified as palliative increased from 51.4 to 66.0% ( P = 0.001), with fewer deaths occurring in the emergency department (17.2–1.4% for the last 3 years, R = 0.75, P = 0.008). The number of aeromedical transfers of patients from KH to tertiary centres decreased from 769 (10.4% of all admissions) in 2011 to 434 (3.4%) in 2018 ( P = 0.006). Conclusions: Increasing the capacity of a remote hospital to provide palliative care allowed more patients to die closer to home and decreased inappropriate aeromedical retrievals. An increased in‐hospital mortality rate should not be misinterpreted as reflecting suboptimal care if palliative intent, patients' wishes and non‐clinical risk factors have not been ascertained.